Anchorage behaviour of headed bars as connection system for precast reinforced concrete structural components. (October 2020) - Singhal, Shubham; Chourasia, Ajay; Parashar, Jalaj
Abstract: Precast reinforced concrete (RC) structural joint is a critical region which demands appropriate connection system for adequate shear transfer. Prevalent dowel bars connection for precast components is prone to damage during the seismic motion. This paper proposes an innovative modified dowel bar connection, termed as headed bars, wherein the reinforcement bars are attached to the steel head anchor through welding and embedded into the concrete. To investigate the anchorage behaviour of headed bars, pull-out tests were conducted on a total of 144 specimens, which were differentiated on the parameters of head profile i.e., plain, grooved, ribbed and without head (representing dowel bar); varying length of the head and varying embedment depth into the concrete. The anchorage behaviour of headed bars was studied from the standpoint of failure mode, bond capacity and slip of bar. Dowel bars demonstrated pull-out failure with low bond capacity, whereas headed bars exhibited slip of bar and concrete failure along with higher bond capacity. Based on the experimental results, geometrical specifications for headed bars are recommended. A numerical analysis was carried out to evaluate the efficacy of headed bars as a connection system, where precast RC wall and columns connected using headed bars of proposed geometry were subjected to displacement controlled lateral loading and compared with the structural performance of connection using conventional dowel bars. Numerical analysis exhibited superior performance of precast RC wall-columns connected through headed bars in comparison to the dowel bar connection.